AKTIVITAS INHIBITOR ALFA GLUKOSIDASE DARI AKTINOMISET ASAL PHYLLOPLANE KELOR (Moringa oleifera) - Noor Andryan Ilsan; Siti Nurfajriah; Maulin Inggriani (Bioma, 2018)
The exploration of alternative natural products is one of the important focus for researcher. Microbes are still the best source for searching the bioactive compounds. Actinomycetes are Gram Positive bacteria which have been known able to produce various of bioactive compounds such as antimicrobials and enzyme inhibitors. The aims of this study were to isolate Actinomycetes from Moringa oleifera phyllosphere also evaluate the antimicrobial and alpha glucosidase inhibitor activities. The result of molecular 16s rRNA gene identification showed FKU 1 isolate had closest related to Nocardia rhamnosiphila. FKU 1 isolate had antimicrobial activities against E.coli, Staphylococcus aureus, Klebsiella pneumonia, K. pneumonia ESBL, dan Vibrio sp. in vitro. FKU 1 also had alpha glucosidase inhibitor activity of 7.50 ± 1.59% at 0.01 µg mL-1 extract concentrations of compared to acarbose (control) of 8.41 ± 0.43%.